Control of mobile manipulator using resolved acceleration with iterative-learning-proportional-integral active force control - Pitowarno, E.; Mailah, Musa (Praise Worthly Prize, 2007)
A practical and novel method to control a mobile manipulator is proposed using a resolved acceleration with iterative-learning-proportional-integral active force control strategy.It is implemented as an approach for the robust motion control of a mobile manipulator comprising a diffrentially driven wheeled mobile platform with a two-link planar arm mounted on top of the platform.The resolved acceleration control is used to manipulate the kinematics of the system in the outermost control loop configuration while the active force control located within the loop is employed to compensate for the dynamic effects including distrurbances and uncertainties.The effectiveness and robustness of the proposed scheme is investigated considering a number of introduced distribances in the forms of impact and vibration forces while the mobile manipulator is performing a trajectory tracking task.The scheme is also validated through an experimental result verify the viability of the proposed scheme in producing the desired robust motion control performances.